A review of national shoulder and elbow joint replacement registries. - Rasmussen, J; Olsen, B; Fevang, B; Furnes, O; Skytta, E; Rahme, H; Salomonsson, B; Mohammed, K; Page, R; Carr, A (2012)
BACKGROUND: The aim was to review the funding, organization, data handling, outcome measurements, and findings from existing national shoulder and elbow joint replacement registries; to consider the possibility of pooling data between registries; and to consider wether a pan european registry might be feasible. MATERIALS AND METHODS: Web sites, annual reports, and publications from ongoing national registries were searched using Google, PubMed, and links from other registries. Representatives from each registry were contacted. RESULTS: Between 1994 and 2004, 6 shoulder registries and 5 elbow registries were established, and by the end of 2009, the shoulder registries included between 2498 and 7113 replacements and the elbow registries between 267 and 1457 replacements. The registries were initiated by orthopedic societies and funded by the government or by levies on implant manufacturers. In some countries, data reporting and patient consent are required. Completeness is assessed by comparing data with the national health authority. All registries use implant survival as the primary outcome. Some registries use patient-reported outcomes as a secondary outcome. CONCLUSIONS: A registry offers many advantages; however, adequate long-term funding and completeness remain a challenge. It is unlikely that large-scale international registries can be implemented, but more countries should be encouraged to establish registries and, by adopting compatible processes, data could be pooled between national registries, adding considerably to their power and usefulness.